New parameters available on Sysmex XE‐5000 hematology analyzers contribute to differentiating dengue from leptospirosis and enteric fever. (3rd September 2015) - Oehadian, A.; Michels, M.; de Mast, Q.; Prihatni, D.; Puspita, M.; Hartantri, Y.; Sinarta, S.; van der Ven, A. J. A. M.; Alisjahbana, B.
Summary: Introduction: Distinguishing dengue virus infection from other febrile thrombocytopenic illnesses such as leptospirosis or enteric fever is important but difficult, due to the unavailability of reliable diagnostic tests. Sysmex XE‐5000 hematology analyzers use fluorescence flow cytometry to quantitate new parameters including cells in the atypical lymphocyte area (AL), high‐fluorescent lymphocyte counts (HFLC), immature granulocytes (IG), and immature platelets (IPF). This study aimed to investigate whether these parameters can help to discriminate between the diseases. Material and methods: We compared hematocytometry performed by a Sysmex XE‐5000 analyzer in Indonesian adults with dengue ( n = 93), leptospirosis ( n = 11), and enteric fever ( n = 6) infection, and in healthy controls ( n = 28). Results: Receiver operating characteristic curves comparing dengue and leptospirosis showed that dengue was characterized by increased %AL (AUC 0.87; 95% CI 0.70–1.03), %HFLC (AUC 0.89; 95% CI 0.78–0.99), and %IPF (AUC 0.81; 95% CI 0.65–0.97), while patients with leptospirosis had increased %IG (AUC 0.86; 95% CI 0.71–1.02). Low %AL, %HFLC, and %IG supported a diagnosis of enteric fever. Conclusions: The detection of AL, HFLC, IG, and IPF by Sysmex XE‐5000 hematology analyzers can help to differentiate between common causes of febrile illnesses with thrombocytopenia in dengue endemic areas. We recommend further investigating the discriminatory value of these parameters in clinical practice.